(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the formation, stages of development, and linguistic features of automotive terminology in modern Chinese. It also comparatively examines scientific research conducted in this field in world and Uzbek linguistics. Methods of term formation, translation problems, and semantic features are scientifically explained.